A Novel Approach in Assessment of Root Canal Curvature - Sadeghi, Shiva; Poryousef, Vahideh (Iranian Endodontic Journal, 2010)
MATERIALS AND METHODS: One hundred and thirty five mesial root canals of mandibular first and second molar teeth were selected. Access cavities were prepared. After inserting a K-file size #10 into each canal, radiographs were taken. Canal curvature was determined by measuring the Schneider angle, canal access angle, as well as the canal radius, length, height and curvature starting distance on scanned radiographs using a computerized image processing system. Data was evaluated statistically using Pearson correlation. RESULTS: The mean canal access angle (CAA) and Schneider angle (S) were 8.04◦ (3.46) and 19◦ (6.99), respectively. The Pearson correlation analysis found significant positive correlation between S and CAA (r=0.826, P<0.0001). Negative correlations were found between radius and length (r= –0.4, P<0.0001), radius and Schneider angle (r= –0.4, P<0.0001), radius and CAA (r= –0.24, P=0.004) and CAA and curvature starting distance (r= 0.4, P<0.0001). There was no correlation between height and distance (r=0.013, P=0.789), as well as CAA and height (r=0.654, P=0.001). CONCLUSION: Under the limitations of this study, the results indicated that the shape of root canal curvature can be more accurately described using two angles, Schneider in combination with Canal access angle. The related parameters included radius, length, distance and height of curvature.